Long-term indices of density of ten woodland Passerine at Eyre Bird Conservatory - Davies, Stephen (Australian Bird Study Association Inc, 2010)
Between 1980 and 2008 surveys of the birds in the vicinity of Eyre Bird Observatory (32º15'S; 126º18'E), in Western Australia have been made almost annually, using a point count method and a mapping method. The results have provided indices of the populations of seven resident, territorial species and three nomadic honeyeaters. Five of the resident species appear to have stable populations, varying over a narrow range, one species, the Blue-breasted Fairywren Malurus pulcherrimus appears to have declined, and one, the Weebill Smicrornis brevirostris, appears to have increased. The honeyeaters fluctuate in numbers greatly, presumably in association with the abundance of flowering mallee, both at Eyre and elsewhere. The results provide some baseline information about the range of fluctuation in numbers that can be expected for common species in mallee woodland at Eyre.